O(s) ciúme(s) em São Bernardo, de Graciliano Ramos, e Grande Sertão: Veredas, de Guimarães Rosa - Borges, Gabriela Brahim Correa (2018)
This paper proposes to discuss jealousy, a feeling that is present, among many others, in two of the most important books of Brazilian literature: São Bernardo and The Devil to Pay in the Backlands. Other aspects that approximate the two novels – such as violence, the women’s death, the first-person and male-voice narrative – had already been analyzed by many scholars of Ramos and Rosa, however, this feeling, so important in the construction of both narratives has not yet received the main attention in a comparative analysis. Thus, our intent is to establish this thematic affinity not only by listing points of similarity, but also by commenting on the distancing conceptions of jealously in the two books – and how these conceptions contribute to a better general comprehension of Ramos’ and Rosa’s books. To do that, we will analyze the relations of the protagonists, Paulo Honorio and Riobaldo, with the women that marked their lives – mainly, but not only, Madalena and Maria Deodorina, (respectively). In this effort, we will discuss the different "modalities" of jealousy mentioned in the narratives above, in order to understand how this theme also touches on other relevant aspects in both cases. cases. For this, notions of psychology, such as Freud's jealousy concepts; or history, like the notions of Patriarchalism of Mary Del Priore, are unavoidable. In addition, other scholars of the novels in question, such as Jaime Ginzburg, Antonio Candido, Roberto Schwarz and Luiz Costa Lima, will also help us in this trajectory. Our objective is, with such analysis, to bring our contribution to the reading of the novels of Graciliano Ramos and Guimarães Rosa, proposing a new approach to jealousy in the construction of both.